DESIGN OF SUPPLY CHAIN MANAGEMENT DISTRIBUTION OF WELDING WORKSHOP MATERIALS AT THE SISU WELDING WORKSHOP - Nike Armaini; Bachtiar Efendi; Sudarmin (Jurnal Teknik Informatika (Jutif), 2022)
Sisu Welding Workshop is a business that provides welding services that utilize raw materials in the form of iron, to meet the needs of raw materials the company chooses materials according to customer orders. become a bottleneck in the production process. The lack of information between the supplier and the company causes the process of distributing iron raw materials to be late, plus errors in the delivery process that are not according to demand causing several shortages of raw materials, as well as the absence of a recording report of incoming and outgoing materials at the company. The purpose of this study is to produce a system that can integrate between the workshop and suppliers to facilitate the process of managing the distribution of welding workshop materials in the form of iron raw materials using the system design development method, namely the waterfall method. This research has implemented a black box testing method. The result of this research is a website-based Supply Chain Management system that can be implemented by the company so as to facilitate the company in the process of managing stock of raw materials and product distribution.